As funções seno e cosseno: diagnóstico de dificuldades de aprendizagem através de sequências didáticas com diferentes mídias - Souza, Edílson Paiva de (2010)
This research aims to diagnose the learning difficulties of high school students about the concepts of the trigonometric functions sine and cosine. The research is based on the principles of Didactic Engineering and on the theory of Semiotic Representation Registers created by Raymond Duval. The didactic sequence presented is oriented by analysis of high school textbooks and considers the research works made using the graphical software in teaching and learning process to improve knowledge. The tools used in the application of the sequence were pencil and paper and software Graphmatic. The sequence was applied with second year students of public high school in the capital of São Paulo. The protocols produced by eight teams of students who participated in four sessions allowed the analysis, and led to the conclusion that the use of technology through a process of education provided by a dynamic graphics software provided an increase in knowledge about the concepts of sine and cosine functions